Essays on trade liberalization and the environment in China - Xu, Fangya (2010)
This thesis is concerned with understanding the relationship between trade liberalization and the environment in the context of China. Four empirical essays are conducted to investigate different aspects of the nexus. We first look at the changing patterns of revealed comparative advantage in manufacturing industries for China and other countries to examine whether dirty industries have `migrated' from developed countries to China as a result of an environmental regulatory gap. The attention is then turned to the determinants of trade specialization and the role played by environmental stringency using cross-industry regressions within a Heckseher-Ohlin framework. The environmental consequences of trade liberalization are evaluated at both the industrial and provincial level. Next, Environmental Input-Output Analysis (EIOA) is used to measure the `potential' and `actual' pollution content (for three air pollutants, C02, SO2, NO, 1) in imports and exports by industry and overall. In the last essay, we evaluate different and countervailing effects (scale, income and trade-induced composition effects) of trade's impact on the environment using Chinese provincial data.